Assessing Reliability of Bending of Concrete Beams Exposed to Freeze-thaw Conditions Based on Compressive Stress Limit Reduction - S.M. Hosseinian; F. Bahmani (Journal of Stress Analysis, 2019)
For existing reinforced concrete structures exposed to freeze-thaw conditions, there is an increasing engineering concernover their remaining safety. This paper presents a novel experimental-theoretical stochastic model for evaluating the reliability of concrete structures subjected to freeze-thaw conditions based on stress limit reduction. Reliability theory and experimental works provide the basis for the model development. Water cement ratio, air content, and number of freeze-thaw cycles are considered as the model variables. Compressive stress limit reduction in freeze-thaw conditions was treated as a stochastic variable. The effectiveness of the proposed model was evaluated using an example concrete structure element. The paper demonstrates that after, for example, 10 years experiencing FT cycles in a cold city; the reliability of the example concrete beam reduces to 52.5 percent for −10◦C concrete freezing temperature. It was found that the results of the proposed method are accurate compared to the literature. It was also found that the results of the proposed method are in good agreement with those obtained based on concrete’s non-destructive tests.